Monosodium Glutamate Treatment Elevates the Immunoreactivity of GFAP and S100β in Caudate Nucleus of the Striatum in Rats - Karol Rycerz; Aleksandra Krawczyk; Jadwiga Jaworska-Adamu; Marcin B. Arciszewski (Biomedicines, 2024)
Background Monosodium glutamate (MSG) in its anionic form, glutamate, is one of the main excitatory amino acids. Excess of this neurotransmitter may lead to excitotoxicity affecting neurons and astrocytes responsible for glutamate metabolism in different brain areas of animals. The aim of the study was to investigate the immunoreactivity of glial fibrillary acidic protein (GFAP) and S100β protein in the caudate nucleus of rats under the condition of elevated glutamate levels. Methods: Fifteen rats were divided into a control group receiving saline and MSG2 and MSG4 groups receiving 2 g/kg b.w. MSG and 4 g/kg b.w. MSG, respectively, for 3 days. An immunohistochemical reaction was conducted on frontal sections containing the caudate nucleus with use of antibodies against GFAP and S100β. Results: Analyses indicated elevated density of astrocytes immunoreactive for the studied proteins in the caudate nucleus in animals receiving MSG. The studied glial cells also demonstrated increased immunostaining intensity for both GFAP and S100β immunoreactive cells especially in the MSG4 group. The number of GFAP-positive processes in astrocytes was similar in all studied groups. Conclusions: The studies demonstrate a potential response of astrocytes to the effect of MSG administration in the caudate nucleus. It was shown that GFAP- and S100β-positive astrocytes in the caudate nucleus may act differently, suggesting distinct roles of these proteins against glutamate excitotoxicity.